GENERATION OF THE ASTHENOSPHERE BY HEAT PRODUCED BY LITHOSPHERIC PLATE MOVEMENT - Maron V.I.; Nikolayevskiy V.N. (My University, 1989)
It is usually assumed that the asthenosphere resulted from partial melting of polycrystalline rocks of the upper mantle. In this connection, it is useful to turn to our earlier formulation of the problem of motion and heat transfer in the atmosphere, where we described the dissipative heating of the matter under the lithospheric plate without assuming an immobile surface of the mesophere that bounds the asthenosphere from below, and where we analyzed the case of unsteady distribution of the temperature and shear rate in a semiinfinite region. In this formulation it can be shown that the dissipative heating of the mantle rocks by large-scale tectonic movements may be one of the ways of generating a fluid asthenosphere. The time interval required for generating the necessary fluidity is 160 million years. Our calculations suggest that the region in which dissipative heating occurs is some zone whose width and depth increase as the square root of the time t. The heat liberated in this zone sharply decreases the viscosity of the rocks and can indeed produce their partial melting. Our correlation between plate movement and melting of the asthenospheric layer gives a qualitative explanation for the local specificity of the asthenosphere under continents and for the relationship between the behavior of the asthenosphere and tectonic activity.